Leisure Time Animation in the Context of Rehabilitation of Juveniles in Youth Detention Centres/Correctional Facilities - Przemysław Frąckowiak; Wioletta Łubkowska; Małgorzata Paczyńska-Jędrycka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
This article is a theoretical study on the role of leisure time animation in the process of rehabilitation of juveniles staying in correctional facilities. The work consists of three parts. The first one presents the structural and functional outline of leisure time institution. The second one deals with the offer of rehabilitation, and the third discusses the role of the pedagogy of fun in the context of rehabilitation and physical education sciences. The study emphasizes the fact that the educational function is implemented mainly in the boarding house of the correctional facility. Classes are held in accordance with a predetermined schedule that is tailored to the individual needs of the pupil. The process of rehabilitation should be assisted by fun (including physical activities). It is therefore necessary to enrich traditional games and fun activities including the newer trends, using, among others, ice-breakers, energizers and team-builders. The implementation of the aforementioned play therefore requires the continuous staff performance improvement in this field. Additionally, games and activities pose the possibility of volunteering, making pupils more sensitive to the needs of others.